A contribution to the update of hydrological standards in West Africa : impacts of climate and Environmental changes on hydrologic extremes - (:unkn) unknown (My University, 2016)
Water resources plays a key role in the social progress and economic development of west african countries. But the mobilization of water is hampered by climate and environmental changes that undergoes the region since 1970. Extremes parts of hydrological regimes are also impacted, but less studies have focus on their evolution, in relation with climate and environmental changes. The main objective of this thesis is to characterize hydrological extreme events in West Africa, we tried to answer the following questions:-What are the trends of maximum discharge in west Africa?-Are these trends due to climate changes or enviromental changes?-Which speculations can be made from these evolutions, according to future climate simulations?In the first part of the work, we analyzed the trends of floods over 14 watersheds of the region. This analysis allowed us to highlight a clustering behavior of flood according to the climatic region the catchments belong to. Increasing trends have been found on flood magnitude and flood frequency of the 3 sahelian catchments used, and decreasing trends of flood magnitude were found on three sudanian catchments. Finally, the remaining catchments did not showed significant trend in their flood regime...
Keywords: African Research